Classification of different Sorghum bicolor genotypes depending on fatty acid composition with using Biplot Analysis - Kokten, Kagan; Kaplan, Mahmut; Temizgul, Ridvan; Beyzi, Selma Buyukkilic; Karaman, Kevser (Progress in Nutrition, 2018)
Seed fatty acid composition and oil content of 61 sorghum genotypes were analyzed by gas chromatography (GC) system and genotypes were classified with Biplot analysis. The fatty acid composition of studied plants showed different saturated and unsaturated fatty acid concentrations. The total oil contents in the seeds of sorghum genotypes ranged from 2.32 to 5.74%. The major fatty acids were found to be linoleic acid (29.85-51.95%), oleic acid (30.62-49.73%), palmitic acid (10.96-22.02%), stearic acid (1.36-7.32%) and linolenic acid (0.58-5.41%), Biplot analysis was utilized to characterize and classify genotypes depending on the fatty acid composition. Two principal components (PCs) were obtained from analysis and determined to be explanatory of more than 82.76% of the total variability in the data set for fatty acids. And also significant negative and positive correlations were found among fatty acids such as between palmitic and stearic acids (r=0.821). The present study is the first report on oil content and fatty acid composition of local sorghum landraces from Turkey.